Learner-Produced Learning Materials: A Step Toward Promoting Learner Autonomy in EFL Grammar Classes - Msimeer, Amal; Elmejie, Eman ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2018)
This paper presents an experimental research study in which the two researchers aim to promote learner autonomy in language learning by means of learner-produced learning materials. The study was conducted at the Department of English in the Faculty of Arts in Misurata, Libya during the academic term-spring 2018. The participants were 50 Libyan students who major in English and they were all enrolled in semester 2 and studied Grammar II course. The participants were required to produce their own learning material which was about a particular grammar item. Semi-structured interviews with the participants were undertaken to know about their reaction towards the experience of taking responsibility to create a learning material, what autonomous strategies they were able to develop while designing the learning materials, what type of learning materials they were able to produce. The findings of the current study revealed that learner autonomy can be fostered in EFL classes in Libya and that Libyan students can develop some autonomous learning strategies. It is concluded that learner-produced learning materials can be a successful and an effective tool to promote learner autonomy in EFL (English as a foreign language) classes.